1993
DOI: 10.4319/lo.1993.38.5.1068
|View full text |Cite
|
Sign up to set email alerts
|

Deep ventilation of Lake Baikal waters due to spring thermal bars

Abstract: Increase of density due to mixing (cabbeling instability) in a spring thermal bar in Lake Baikal results in the sinking of cold surface water (T = 3.2−3.4°C, w = 0.3 cm s−1) below the profile of Tmd. This density increase generates forced convection and subsequent movement of cold water along the underwater slope to maximum depths. Cooling of deep and near‐bottom waters caused by forced convection is compensated during other seasons of the year by eddy heat flux directed toward the bottom. On a long‐term basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(153 citation statements)
references
References 3 publications
2
151
0
Order By: Relevance
“…After heavy precipitation, CR A increases to several hundreds to thousands of grams per meter, increasing the river water density and river intrusion depths. During winter, T A drops usually below the temperature of maximum density (T md = 4°C), causing cabbeling instability [Carmack et al, 1979;Shimaraev et al, 1993]. The cold river front mixes with warmer lake water, leading to temperatures close to T md resulting in density-driven intrusions into the deep water.…”
Section: Intrusion Depths Of Aare and Lü Tschinementioning
confidence: 99%
“…After heavy precipitation, CR A increases to several hundreds to thousands of grams per meter, increasing the river water density and river intrusion depths. During winter, T A drops usually below the temperature of maximum density (T md = 4°C), causing cabbeling instability [Carmack et al, 1979;Shimaraev et al, 1993]. The cold river front mixes with warmer lake water, leading to temperatures close to T md resulting in density-driven intrusions into the deep water.…”
Section: Intrusion Depths Of Aare and Lü Tschinementioning
confidence: 99%
“…1) because the observation is largely affected by many other factors such as the bottom topography and the current due to river discharge (Shimaraev et al, 1993), which are excluded from the present experiments. Nevertheless, some similarities are found between both results.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Lake Baikal in Russia and Crator Lake in U.S.A., deep water ventilation occurs down to the bottom and appears to be caused by deep convection Weiss et al, 1991;McManus et al, 1993;Shimaraev et al, 1993). For example, in Lake Baikal, higher concentrations of dissolved oxygen and chlorofluorocarbons (CFCs) has been observed in the bottom water than in the overlying water .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to extensively assess environmental impacts on Lake Baikal, their recent and their longer-term history, and their potential influence into the future, it is important to have comprehensive knowledge on the forcing mechanisms and processes, which are responsible for these changes. Research papers of different scientific disciplines have contributed background knowledge on the formation of Lake Baikal and the dynamics of its vast water mass (Goldyrev, 1982;Bezrukova et al, 1991;Shimaraev et al, 1993;Khozhova and Izmest'eva, 1998). It has been shown that biological, physical and geochemical processes all influence biological and geochemical variability in the lake Flower, 1998;Müller et al, 2005;Granina and Callender, 2007;Schmid et al, 2008).…”
Section: Introductionmentioning
confidence: 99%